Amino Acids in Cerebrospinal Fluid of Patients with Aneurysmal Subarachnoid Haemorrhage: An Observational Study - Sokół, Bartosz; Urbaniak, Bartosz; Wąsik, Norbert; Plewa, Szymon; Klupczyńska, Agnieszka; Jankowski, Roman; Więckowska, Barbara; Juszkat, Robert; Kokot, Zenon (Frontiers in Neurology, 2017)
Background The authors are aware of only one article investigating amino acid concentrations in cerebrospinal fluid (CSF) in patients with ruptured intracranial aneurysms, and this was published 31 years ago. Since then, both management of subarachnoid haemorrhage (SAH) and amino acid assay techniques have seen radical alterations, yet the pathophysiology of SAH remains unclear. Objective To analyse the pattern of concentrations of amino acids and related compounds in patients with different outcomes following aneurysmal SAH. Methods 49 CSF samples were collected from 23 patients on days 0–3, 5, and 10 post-SAH. Concentrations of 33 amino acids and related compounds were assayed by liquid chromatography tandem mass spectrometry in patients with good [Glasgow Outcome Scale (GOS) 1–3] and poor (GOS 4–5) outcome. Results Of the 33 compounds assayed, only hydroxyproline and 3-aminoisobutyric acid appeared not to increase significantly following SAH. In poor outcome patients, we found significantly higher concentrations of aspartic acid (p = 0.038), glutamic acid (p = 0.038), and seven other compounds on days 0–3 post-SAH; glutamic acid (p = 0.041) on day 5 post-SAH, and 2-aminoadipic acid (p = 0.033) on day 10 post-SAH. The most significant correlation with GOS at 3 months was found for aminoadipic acid on day 10 post-SAH (cc = −0.81). Conclusion Aneurysmal rupture leads to a generalised increase of amino acids and related compounds in CSF. The patterns differ between good and poor outcome cases. Increased excitatory amino acids are strongly indicative of poor outcome.